Humanitarian “Reversing” in the Education Development in the Russian Federation Education under the Conditions of Transhumanistic Challenges in the Era of Globalisation - Kochetkov, Maksim V.; Avdeeva, Elena A. (International Journal of Criminology and Sociology, 2021)
The effectiveness of the development of individual countries within the conditions of accelerating scientific and technological progress, expanding the influence of globalisation and integration processes in the global socio-cultural space are very important during the exchange of international students. The purpose of the paper is to research the methodological foundations of the humanities education for international students as an alternative to transhumanist ideology. In the framework of general scientific research methods, a paradigmatic approach is used as a factor analysis of students' educational processes. Particular attention is paid to the substantiation of the methodological foundations of the education humanisation on the basis of modern ontologically anthropological and religious-anthropological achievements of the philosophical field of knowledge. In this regard, the thesis is accepted that the artificially imposed transhumanist ideology performs a key integrating function when considering the practice of education of international students. The novelty of the study is due to a discussion of the contradictions caused by all-round technocratisation and informatisation, the fall of moral standards, and the degradation of human behavior. The practical significance of the study is determined by the need to develop a different pedagogy and model of education for modern students.